Degradation kinetics of ethylene propylene diene terpolymer residues devulcanized by microwaves. (February 2014) - Pistor, Vinicius; Zattera, Ademi J
The reclaiming of elastomer residues is one of the main problems of recycling materials. In this work, the efficiency of devulcanization of recycled ethylene propylene diene terpolymer (EPDM) was determined by subjecting the elastomer samples to 2, 3 and 4 min of microwaves exposure. Scanning electron microscopy and thermogravimetric analysis using different heating rates to determine the kinetic degradation parameters according to the Flynn–Wall–Ozawa and Criado methods were studied. The results obtained showed that up to 4 min devulcanization exposure period, the degradation temperature of EPDM did not exceed. Microwaves exposure caused modifications in the morphology and reduction in activation energy values upon increased samples exposure period. Degradation mechanisms were altered, mainly for the 4-min exposure period, where the nucleation mechanism shifts to diffusion, suggesting that the microwave method was able to promote the breakage of the elastomeric three-dimensional network.